EFEK BERKUMUR EKSTRAK PEGAGAN (Centella asiatica (L.) Urban) KONSENTRASI 40% DAN 50% TERHADAP AKTIVITAS SPESIFIK GLUTATHIONE S-TRANSFERASE PADA SALIVA PENDERITA GINGIVITIS SEDANG - Dhika Paramita Prameswari; Juni Handajani (Faculty of Pharmacy, Universitas Gadjah Mada, 2010)
Glutathione S-transferase (GST) is enzyme in saliva that catalyzes the nucleophilic conjugation reaction of glutathione (GSH) with many diverse electrophilic substrates and has major mechanism in detoxification process of xenobiotics. Pegagan (Centella asiatica (L.) Urban) is contain flavonoid as a xenobiotic component that have an ability to inhibit the specific activity of GST. This study was aiming to understand the effect of gargling with centella’s extract concentration 40% and 50% to inhibit the specific activity of GST in saliva of gingivitis patient. Under ethical clearance from local Ethics Committee from Medical Faculty, Gadjah Mada University, 30 patients of moderate ingivitis divided into two groups: 20 person as treated group were instructed to gargle centella’s extracts concentration 50% and 60%, and 10 person as positive control group was given Hexetidine 0.1%. Every subject was gargling as much as 5 ml every morning (after woke up) and every night (before sleeping) for 5 days constitutively. Saliva was collected before and after treatment. GST’s specific activity was measured using spectrophotometer at 340 nm wavelength and gingivitis status was using Gingival Index (GI). This study showed that using centella’s extract concentration 50% could down regulate the GST’s specific activity saliva and GI score. In conclusion, centella’s extract concentration 50% was indicating better compare with concentration 40% to accelerate of gingivitis healing.